2011
DOI: 10.1016/j.intmar.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

How Much can you Trust Online Information? Cues for Perceived Trustworthiness of Consumer-generated Online Information

Abstract: Consumers increasingly rely on the Internet to obtain product information and advice from other consumers. However, since the information available on the Internet is easily manipulated, they have to seek cues for the trustworthiness of the online information. The present study proposes and tests the effects on perceived trust of online information and subsequent attitude of (1) perceived strong vs. weak social relationships among net pals and (2) positive vs. negative messages. The moderating effects of crede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(172 citation statements)
references
References 37 publications
8
158
2
4
Order By: Relevance
“…Consumers need cues to evaluate the relevance and trustworthiness of product-and brand-related information on social networking sites (Pan and Chiou 2011). If the user believes and adopts the recommendations, it will result in a change of attitudes, beliefs and actions (Chang and Wu 2014).…”
Section: General Discussion Summary and Implications Of The Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers need cues to evaluate the relevance and trustworthiness of product-and brand-related information on social networking sites (Pan and Chiou 2011). If the user believes and adopts the recommendations, it will result in a change of attitudes, beliefs and actions (Chang and Wu 2014).…”
Section: General Discussion Summary and Implications Of The Findingsmentioning
confidence: 99%
“…Jahn and Kunz (2012) focus on Facebook fan page participation and its impact on the customer brand relationship. A study by Pan and Chiou (2011) tests the effects of strong vs. weak social relationships and positive vs. negative messages on perceived trust of online information in a discussion forum. However, empirical studies on the consequences of brand-related comments by Facebook users as a specific manifestation of CEB remain scarce.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Related research has also investigated the criteria consumers use when choosing a specific on-line retailer. Some have noted the role of trust and the increasing importance of the brand (Burt 2010;Büttner and Göritz 2008;Huang et al 2004;Mukherjee and Nath 2007;Pan, and Chiou, 2011) while others have identified operational issues as being an important determinant of loyalty. Policies and procedures relating to delivery times, item substitutions and product returns all have the potential to become sources of competitive advantage (Bonifield et al 2010;Chatterjee 2010;Doherty et al 1999;.…”
Section: E-commerce and Consumer Behaviourmentioning
confidence: 99%
“…HenningThurau et al (2004) define eWOM communication as any positive or negative statement made by customers -potential, real or former -about a product or company, which is made available to other people via the Internet. This definition and its theoretical categorisation are widespread in the literature (Cheung et al 2009;Jeong and Jang 2011;Pan and Chiou 2011;Smith, Fischer, and Yongjian 2012;Vilpponen, Winter, and Sundqvist 2006). eWOM exhibits important differences with respect to traditional WOM communications.…”
Section: Literature Reviewmentioning
confidence: 99%